Feminisme Sabirin dalam Novel An-Nida, Al-Khalid Ikon Revivalisme Perempuan Mesir - Latifi, Yulia Nasrul (Musawa Jurnal Studi Gender dan Islam, 2010)
The material object of this writing is Najib Kylani's novel, An-Nida' al-Khalid, and the formal object is feminism literary criticism. For getting the idea of icons, this writing needs the sociology of literature, because the literature is the mirror of the reality. Of importance in this novel is its difference with the other modem Egyptian novels, that usually, the image drawn of women by Arab novelists and poets is the drawing of women who remain subjugated to men by the patriarchal system. The heroine in this novel, namely Sabirin, is described the strong and positive personality, mature, smarth, and used to participate in politics. In her letter, Sabirin campaigned against patriarchal system and the freedom of women as an humanbeing like a men. Her patriotic an enlightened ideas is the icon of Egyptian's women revivalisme in the early twenty century. Like Sabirin, these pioneers campaigned and called upon the Egyptian's women to fight all the limitations imposed upon their independence. They realize that the cause of women's emancipation was one of the crucial fronts in the struggle against backwardness and internal reactionary forces.